Combined repetitive transcranial magnetic stimulation and medication treatment for depression is associated with serum amyloid a level: Evidence from naturalistic clinical practice - Xu, You; Han, Li; Wei, Youdan; Mao, Hongjing; Yu, Zhenghe (Frontiers in Neuroscience, 2022)
Objective: Repetitive transcranial magnetic stimulation (rTMS) has a positive effect on patients with depressive disorder, while the underpinning molecular mechanisms is unknown. Here, we aimed to investigate the effect of rTMS on serum levels of serum amyloid A (SAA) and testosterone in a real-world setting. Methods: Ninety-seven patients with depressive disorder were treated with medicine and rTMS (rTMS group) while 122 patients treated using medicine only (Control group). Plasma levels of SAA and testosterone were measured before and after two weeks treatment, and treatment effect was evaluated by Hamilton Rating Scale for Depression (HAMD). Results: The treatment effects revealed by both total HAMD score and the percentage of HAMD decrease at the second week was significantly greater in rTMS group compared to control group. No significant difference was found for SAA nor testosterone level between two groups. However, the percentage of changes in SAA (r = -0.492, p = 0.017) at the second week was significantly correlated with the percentage of decrease in HAMD score in rTMS group but not in control group. Conclusions: Patients with depression benefits more from combined rTMS and medication treatment in this naturalistic study. Changes in SAA level, but not testosterone level, were related to depressive remission after two weeks’ combined treatment.